THE EFFICACY OF USING ARTS AND SPECIFICALLY MUSIC IN THE ENGLISH LANGUAGE CLASSROOM - Jonida PETRO (Association of Social and Educational Innovation, 2023)
The focus of this article is to analyse art's contribution to the effectiveness of English learning through a thorough look of art's use, in particular music and songs, in the English language classroom. More in depth, it looks also at the benefits and shortcomings of utilizing art techniques to teach English, as well as to identify ideas and tools that can assist teachers and students in overcoming the current challenges to using art in English classrooms. While the arts are still not widely regarded as important educational and supplementary tools in a variety of teaching and learning contexts in Albania, this is particularly true in English language teaching as it offers several potential ways to improve both the planning and implementation of traditional English language teaching methods. Learning a foreign language can be distressing, in particular during the teenage hood. The period when students are adjusting to the new social and emotional changes, certainly does not simplify the new language learning. That is why the study was mainly focused on this particular age-group, aiming to identify art as a tool to be utilised at the benefit of both teachers and students in the English learning process. Song and music are helpful language learning instruments that enhance second language instruction without putting too much academic burden on the students. They have been shown to be a good listening exercise with several advantages, offering a learning atmosphere that avoids classroom tension while yet serving the aim of learning through entertaining activities.